Assessing the employees’ efficiency and adaptive performance for sustainable human resource management practices and transactional leadership: HR-centric policies for post COVID-19 era - Ismail AlAbri; Rusinah bte Siron; Samar Alzamel; Hamood Al-Enezi; Mui Yee Cheok (Frontiers in Energy Research, 2022)
The utilization of sustainable organizational human resource management (HRM) practices as predictors of adaptive performance has received little attention, despite the importance of adaptive performance in improving organizational efficiency. This study explores the relationship between HRM activities (training, performance appraisal, job enlargement, employee involvement, and work enrichment) and employees’ adaptive performance using the resource-based view (RBV) theory. It also looked into the role of transactional leadership in regulating these correlations to draw up the policies for the post-pandemic era. A quantitative study is conducted and a questionnaire was distributed randomly among the Ministry of Health of the Sultanate of Oman and 233 people have participated in the questionnaire survey. PLS-SEM was utilized to analyze the data. In this study, performance appraisal, job enlargement training, and work enrichment all have a considerable influence on employees’ adaptive performance. Furthermore, transactional leadership moderates the linkage between job enrichment and employee adaptive performance. As a result, the higher the organization’s attention on certain HR policies, the better their adaptive performance. HR practices are important predictors of adaptive performance; thus, managers and practitioners should take into account workers’ adaptability to encourage more adaptive behavior in the workplace. This article further discusses the study’s weaknesses as well as future research directives on HRM practices and adaptive performance.